THE IMPACT OF AI COPILOTS ON COGNITIVE LOAD IN ENGLISH LANGUAGE LEARNING - Said-Fozilkhon Akmalkhonovich Akmalkhonov (Western European Studies, 2025)
In the context of rapid digitalization of education, the use of artificial intelligence (AI) in foreign language learning is gaining increasing significance. This study examines the impact of AI copilots such as ChatGPT and Grammarly on cognitive load, the quality of written English, and the level of student engagement in the learning process. The experiment was conducted among tourism faculty students with A2–B1 English proficiency, enrolled in an "English for Academic Purposes" course. The results revealed that the use of AI tools contributed to improved lexical and grammatical features of students’ texts, enhanced structural coherence, and reduced error rates. However, the study also identified certain risks: a decrease in the depth of material processing, standardization of writing style, and weakening of independent cognitive activity. Based on these findings, the necessity of fostering students’ critical digital literacy and developing pedagogical models that balance technological assistance with learners’ autonomy is emphasized. This research contributes to the emerging field of digital pedagogy and highlights the importance of a mindful approach to integrating AI into English language education
Keywords: AI copilots; cognitive load; digital pedagogy